ANALISIS DISKREPANSI PEMANFAATAN RAPOR PENDIDIKAN PADA JENJANG SEKOLAH DASAR SESUAI PERMENDIKBUDRISTEK N0.9 TAHUN 2022 - Handayani, Baiq Vina (Adi Widya: Jurnal Pendidikan Dasar, 2025)
This study aims to identify the level of gap in the use of education report cards as the basis for data-based planning at the elementary school level in Ampenan District, NTB Province, as mandated in Permendikbudristek Number 9 of 2022. The approach used is qualitative descriptive with a gap evaluation model. Data collection was carried out through questionnaires and observations of 25 educators and education personnel (PTK) who were randomly selected, consisting of school principals, teachers, and school operators. The data was analyzed using the Wilcoxon graded mark test to measure the difference and the size of the gap to the established standard. The results of the study show that the gap in all stages of the use of education report cards is relatively small. The details are as follows: (1) the implementation of AN has a small gap with a difference of 0.8; (2) identification of service conditions using education report cards there is a small gap with a difference of 0.71; (3) reflection on determining the focus of service improvement for the next year there is a small gap with a difference of 0.68; (4) the preparation of learning planning according to the data on the education report card there is a small gap with a difference of 0.75; (5) mapping the need for competency improvement so that educators and education personnel (PTK) are able to carry out service improvements, there is a small gap with a difference of 0.6; (6) the preparation of RKT and RKAS according to the improvement priorities on the Education Report Card there is a small gap with a difference of 0.58; (7) the implementation of the activity planning that has been prepared there is a small gap with a difference of 0.87; (8) Revision of planning and budgeting based on the results of reflection there was a small gap with a difference of 0.62.